Investigation on the roles of equilibrium toroidal rotation during edge-localized mode mitigated by resonant magnetic perturbations - DONG, Liangkang; CHEN, Shaoyong; MOU, Maolin; LUO, Yang; QIN, Chenchen; TANG, Changjian (Plasma science & technology, 2024)
The effects of equilibrium toroidal rotation during edge-localized mode (ELM) mitigated by resonant magnetic perturbation (RMP) are studied with the experimental equilibria of the EAST tokamak based on the four-field model in the BOUT++ code. As the two main parameters to determine the toroidal rotation profiles, the rotation shear and magnitudes were separately scanned to investigate their roles in the impact of RMPs on peeling–ballooning (P-B) modes. On one hand, the results show that strong toroidal rotation shear is favorable for the enhancement of the self-generated shearing rate with RMPs, leading to significant ELM mitigation with RMP in the stronger toroidal rotation shear region. On the other hand, toroidal rotation magnitudes may affect ELM mitigation by changing the penetration of the RMPs, more precisely the resonant components. RMPs can lead to a reduction in the pedestal energy loss by enhancing the multimode coupling in the turbulence transport phase. The shielding effects on RMPs increase with the toroidal rotation magnitude, leading to the enhancement of the multimode coupling with RMPs to be significantly weakened. Hence, the reduction in pedestal energy loss by RMPs decreased with the rotation magnitude. In brief, the results show that toroidal rotation plays a dual role in ELM mitigation with RMP by changing the shielding effects of plasma by rotation magnitude and affecting by rotation shear. In the high toroidal rotation region, toroidal rotation shear is usually strong and hence plays a dominant role in the influence of RMP on P-B modes, whereas in the low rotation region, toroidal rotation shear is weak and has negligible impact on P-B modes, and the rotation magnitude plays a dominant role in the influence of RMPs on the P-B modes by changing the field penetration. Therefore, the dual role of toroidal rotation leads to stronger ELM mitigation with RMP, which may be achieved both in the low toroidal rotation region and the relatively high rotation region that has strong rotational shear.